Penggunaan PBBK(Pembelajaran Bahasa Berbantukan Komputer) dalam pengajaran dan pembelajaran Bahasa Arab sebagai bahasa asing: satu tinjauan awal. - Ashinida Aladdin,; Afendi Hamat,; Mohd. Shabri Yusof, (Penerbit UKM, 2004)
Due to the rapidly evolving field of ICT, its influence is felt strongly in almost every other discipline, including education. This research of using computer assisted language learning (CALL) in teaching and learning Arabic language is a preliminary research which was done on 40 Arabic language teachers from three religious boarding school in Malaysia namely Kolej Islam Sultan Alam Shah, Kelang, Sekolah Menengah Agama Persekutuan, Kajang and Sekolah Menengah Agama Persekutuan, Labu. This is basically a descriptive study conducted with the use of surveys via questionnaires. To obtain the data, questionnaires were distributed among the samples and were analyzed descriptively. This study aims to gauge the scope of use of computers in the teaching and learning of Arabic in the schools mentioned above. The study collected feedback from Arabic language teachers on their perception, level of readiness and understanding of their roles in the use of CALL in their schools. The initial findings indicate a very good level of perception and attitude among the teachers surveyed. The study also finds high level of readiness among the teachers to undergo training in order to prepare themselves for the use of CALL. Overall, the findings indicate an encouraging environment for the implementation of CALL in the teaching and learning of Arabic at the schools surveyed.